The Effect of Motivation, Work Environment and Workload on Employee Performance of PT Bumimas Multikarya Perkasa - Azizatul Laili; Sukaris sukaris (Universitas Muhammadiyah Gresik, 2022)
The background of this research is that the performance of employees at PT Bumimas Multikarya Perkasa has decreased. This study aims to test the influence of motivation, work environment, and workload on the performance of employees of PT Bumimas Multikarya Perkasa Production. This research uses quantitative methods. The population in this study was the production employees of PT Bumimas Multikarya Perkasa, which amounted to 85 people, while the sample was taken using the Non Probability Sampling technique using a saturated sample. The reason is because the sampling from a population of less than 100. The sample studied by the researcher is 85 employees of PT Bumimas Multikarya Perkasa. The analysis technique uses instrument testing, classical assumption test, and hypothesis testing. For the test tool, the Statistical Package for the Social Sciences (SPSS) is used. The results of this study indicate that motivation, work Environment have a positive, and workload has a negative and significant effect on employee performance.